KEEFEKTIFAN MODEL JIGSAW TERHADAP HASIL BELAJAR IPA SISWA KELAS IV (Universitas Negeri Semarang, 2016)
The problems research are whether the learning model Jigsaw more effective against result learning IPA material Natural Resources grade IV student SDN Cluster Dewi Sartika Pati. The purpose of research is to determine the effectiveness of the learning model Jigsaw against learning outcomes IPA material Natural Resources in grade IV SDN Cluster Dewi Sartika Pati. Forms of this study was Quasi Experimental Design with design Nonequivalent Control Group Design. The population in this study were all students in grade IV SDN Cluster Dewi Sartika Pati. Sampling using random cluster sampling and selected primary schools Soneyan 03 as an experimental group and a primary school Soneyan 01 as the control group. The data collection technique of learning outcomes using multiple choice tests, field notes, and documentation. Learning outcomes data were analyzed by t-test and the n-gain. The results showed that the average value posttest experimental class is greater than the control class. The average value posttest experimental class 77.88, while the control class 70.75. T test results showed thitung 7.7583, while ttabel 2.07. Because thitung ttable, it can be concluded that result learning using jigsaw learning model more effective against result learning IPA material Natural Resources grade IV student SDN Cluster Dewi Sartika Pati.